Targeting Autophagy in Cancer: Recent Advances and Future Directions - Amaravadi, Ravi K. (Cancer Discov, 2019)
Autophagy, a multistep lysosomal degradation pathway that supports nutrient recycling and metabolic adaptation, has been implicated as a process that regulates cancer. Although autophagy induction may limit the development of tumors, evidence in mouse models demonstrates that autophagy inhibition can limit the growth of established tumors and improve response to cancer therapeutics. Certain cancer genotypes may be especially prone to autophagy inhibition. Different strategies for autophagy modulation may be needed depending on the cancer context. Here, we review new advances in the molecular control of autophagy, the role of selective autophagy in cancer, and the role of autophagy within the tumor microenvironment and tumor immunity. We also highlight clinical efforts to repurpose lysosomal inhibitors, such as hydroxychloroquine, as anticancer agents that block autophagy, as well as the development of more potent and specific autophagy inhibitors for cancer treatment, and review future directions for autophagy research.